Variability of the photoperiod response in guar (Cyamopsis tetragonoloba (L.) Taub.) genotypes of different geographic origin - S. B. Teplyakova; V. A. Volkov; E. А. Dzyubenko; E. К. Potokina (Вавиловский журнал генетики и селекции, 2019)
The introduction of the new legume crop guar is of great practical importance for Russia, since it serves as a source of valuable vegetable raw material, guar gum, used for the food, gas and oil industry. The main problem with guar cultivation in the southern regions of the Russian Federation is that this plant should be grown under a short photoperiod. Prolonged daylight exposure is an obstacle to the timely transition of guar to flowering, which dramatically affects its productivity. In the study, 192 guar genotypes from the VIR collection were tested for the speed of transition to flowering on an extremely long photoperiod (18.2–18.9 h) in the greenhouse of the Pushkin experimental station of VIR (St. Petersburg). At the same time, the earliness of maturation of the same genotypes was estimated under  the field conditions in the Kuban experimental station  of VIR (Krasnodar area). Among the samples  tested, genotypes with weak photoperiodic sensitivity (which were also early maturated under  the conditions of Krasnodar), as well as the  highly photoperiod-sensitive genotypes were identified.  It has been  established that  for the same guar plant the critical photoperiod initiating the formation  of buds may not coincide with the critical photoperiod required for their flushing (i. e. flowering per se). The observed fact confirms the hypothesis reported earlier about a two-stage launch of the flowering program in guar, according to which budding and flowering itself are controlled by independent gene  systems. According to our results, the successful breeding of early mature guar varieties ultimately depends on the first gene system that controls the initiation of budding in response to a critical photoperiod. We suggest that another hypothetical gene  system can influence the dates  of guar flowering, which determines the speed  of vegetative development of a specific genotype, measured as the number of days from germination to the appearance of the first true leaf. Thus, sensitivity to photoperiod in guar is only one of several factors that determine the speed  of a plant’s transition  to flowering, and it should not be assessed on the basis of the length  of the period from germination to flowering, which is common in breeding practice. The results of the study show that, although the photoperiod sensitivity of guar limits the range of geographic latitudes in which the legume  crop can be successfully grown, there  is a real opportunity to overcome this limitation  by selecting  and propagating photoperiod-insensitive genotypes from the enormous genetic diversity of this species.